Quenching of myosin intrinsic fluorescence unravels the existence of a high affinity binding site for decavanadate - Aureliano, M. (2014)
Decavanadate, one of the aggregated species of vanadate, is a potent inhibitor of several enzymes, includingskeletalmusclemyosin.However,itsputativebindingsitesinmyosinarelargelyunknown. Titration of the intrinsic fluorescence of myosin, purified from rabbit skeletal muscle, have been carried out in 0.3 M KCl, 5 mM CaCl2 and 25 mM Tris-HCl (pH 7.0), with 0.1 mg/ml myosin. In the 0–200M total vanadate concentration range, decavanadate produced approximately 25% quenching of the intrinsic fluorescence of myosin, with an apparent dissociation constant in the micromolar range. This effect was found to be specific of decavanadate, because titration with metavanadate up to 200M did not produce a significant quenching of the intrinsic fluorescence of myosin. This quenching was accompanied by a parallel decrease of the accessibility of myosin tryptophans to the water-soluble collisional quencher KI, with an apparent dissociation constant also in the micromolar range. It is concluded that the binding of decavanadate to high-affinity sites in myosin produces local conformational change(s) near the tryptophans more accessible to water in the three-dimensional structure of this protein.